Posibilities of increasing the performances in human resources domain from the perspective of psychosocioprofesional reengineering - Filip, Elena (НТУ "ХПИ", 2010)
The most important conclusion of this analysis is that realizing the report between possibility and necessity resulted that there already are the conditions for another type of projection to the human resources management. If until now we were mostly preoccupied by the tactical aspect of the human resources issue, now we consider that it is time for a change of approach.

Наиболее важный вывод из этого анализа, что для реализации проблемы, описанной в статье от возможности и необходимости, уже есть условия для другого типа проекции на человеческие ресурсы управления. Если до сих пор мы были в основном озабочены тактическим аспектом вопроса человеческих ресурсов, в настоящее время мы считаем, что настало время для изменения подхода.
Возможности повышения продуктивности в развитие людских ресурсов домейна с точки зрения психолого- социального профессионального реинжиниринга